Is Dodd Frank orderly liquidation authority necessary to fix too-big-to-fail? - Paul H. Kupiec (American Enterprise Institute (AEI), 2015)
The Dodd-Frank Act (DFA) Orderly Liquidation Authority (OLA) has many legal issues that could prevent its use. Should there be a next financial crisis, regulators may again be forced to sell a large failing bank to a larger banking institution, creating yet another too-big-to-fail (TBTF) institution. Regulatory plans for using OLA focus on injecting parent holding company capital into the critical operating subsidiaries of systemically important financial institutions (SIFIs) to keep these subsidiaries open and operating. This goal can be achieved without OLA by imposing substantially higher minimum capital requirements on critical operating subsidiaries instead of imposing them on parent SIFIs. But, replacing OLA with this simple alternative, alone, will not solve the TBTF problem. Investor perceptions of TBTF arise naturally given flaws in the existing deposit insurance bank resolution process, and the predilection for regulatory forbearance created by conflicting responsibilities assigned to the Federal Reserve Board (FRB). The FRB duty to be the consolidated supervisor of largest BHCs and other designated SIFIs, the guardian of financial stability, and the lender of last resort make it rational for investors to expect large financial institution to receive special assistance to forestall their failure or protect their creditors from loss. In contrast, other institutions that offer similar financial services will be allowed to fail and impose losses on similarly situated creditors. To end TBTF, financial regulation must be refocused on: (i) ensuring the uninterrupted operation of important subsidiaries by increasing capital requirements on banks and critical functionally-regulated affiliates - not parent holding companies; (ii) reforming the deposit insurance bank resolution process to mandate the break-up of large failing banks; (iii) removing the regulatory structure that creates TBTF investor expectations; and (iv) requiring SIFI parent companies to reorganize or liquidate using a judicial bankruptcy process in which similarly situated creditors are treated equally. The alternative approach of higher capital requirements at operating subsidiaries does not require OLA or new regulations to operationalize OLA-rules requiring minimum total loss absorbing capacity or contingent convertible debt. If higher capital requirements at critical subsidiaries are funded with debt issued by the parent holding company, there will be no reduction in SIFIs' consolidated interest tax shields and consequently no increase in the cost of commercial and consumer credit. These reforms will simplify regulation, improve transparency, protect taxpayers from the expense of future SIFI bailouts and eliminate the TBTF subsidy without abridging property rights and legal protection for parent SIFI creditors.
Keywords: A; 330; Dodd-Frank Act; too big to fail